Relationship Between Nutritional Status, Breakfast Pattern, And Sleep Time On Work Efficiency: A Cross-Sectional Study Of Posyandu Cadres In Limbung Village - Neila Sari Lazuli; Marlenywati, Marlenywati; Elly Trisnawati (Jurnal EduHealth, 2025)
Posyandu cadres play an important role in public health services, but their work productivity is often affected by various basic health factors, such as nutritional status, breakfast habits, and sleep quality. This study aimed to analyse the relationship between these three factors and the productivity of Posyandu cadres in Limbung Village. Using a quantitative approach with a survey method, the data was analysed with the help of SPSS. The results showed a significant relationship between nutritional status and productivity, where cadres with normal nutritional status had higher productivity than those who were overweight or obese (p=0.016). Breakfast habit also had a positive influence (p=0.009), with cadres who habitually ate breakfast showing better productivity. In addition, good sleep quality significantly improved cadre work productivity (p=0.001).This study highlights the importance of a holistic approach in supporting cadre work productivity, with a focus on nutrition education, healthy breakfast campaigns, and improved sleep quality. The findings are expected to inform practical interventions to improve the performance of Posyandu cadres and strengthen the public health care system.